BLOCKCHAIN SOLUTION FOR THIRD PARTY ADMINISTRATOR PROCESS IN HEALTH INSURANCE MEDICAL CLAIMS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
India has a vast population of 1.3 Billion  people out of which approximately 44% have  a health insurance policy 1. In the FY 2017-18  alone, there were approximately 4.7 million  Indians who claimed mediclaim insurance  for hospitalization done which included both  pre-planned as well as emergency visits to the  hospital 2. Each of these claims took around  4-6 hours of processing and follow-up time  costing hugely to the claimants 3. The objective  of this paper is to evaluate the reduction in Turn  Around Time (TAT) and thereby reduce costs  in terms of man-hours saved by effective use of  Blockchain for the purpose of settling claims.
Keywords: Third Party Administrators; Blockchain; Mediclaim